THE ENHANCEMENT OF INFERRING skill and CONCEPT mastery IN BASIC THERMOCHEMISTRY SUBJECT by LEARNING CYCLE 5E MODEL - wirda ningsih turnip; ratu betta rudibyani; chansyanah diawati (Universitas Lampung, 2012)
This research is intended to describe the effective characteristics of learning cycle 5E (LC 5E) teaching method in increasing students’ inferring skill and concept mastery in basic termokimia subject of SMA Negeri 6 Bandar Lampung. The samples of this research were the XI IPA2 as control class and the XI IPA3as experimental class. Purposive Sampling Technique was implemented to choose the samples of this research. Quasi Experimental Method by implementing Non Equivalent Control Group Design was employed in this research. The effectiveness of LC 5E teaching method was measured based on the significant level of n-gain increase. The result shows that the average of n-gain for inferring skill in control class and experimental class were 0,12 and 0,43; while the average of n-gain in concept mastery in control class and experimental class were 0,13 and 0,53. This fact shows that LC 5E teaching method is more effective in increasing students’ inferring skill and concept mastery in basic termokimia subject.Key words : LC 5E, inferring skill and concept mastery